Transtornos mentais em profissionais da saúde no enfrentamento da COVID-19 - Faria, Maxwell de Souza (2023)
Introduction: The COVID-19 pandemic is considered one of the most serious health crises on a global scale, and its effects on the mental health of health professionals who worked in patient care are of fundamental importance, as they played a relevant role in the care and management of the disease, being susceptible to psychological distress, leading to the emergence of common mental disorders, anxious and depressive conditions in their work environment. Objective: To investigate the prevalence of self-perceived mental disorders in health professionals who have worked to combat the novel coronavirus. Material and Method: Questionnaires were used to screen for Common Mental Disorders (CMD) using the Self-Reporting Questionnaire 20 (SRQ-20), and to indicate Anxiety and Depression, the Hospital Anxiety and Depression Scale (HAD). This is a quantitative, descriptive, correlational and cross-sectional study carried out with health professionals from a medium and high complexity hospital in the interior of São Paulo. Results: Among the 51 health professionals, 80.4% were women, with an average age of 33. The prevalence of CMD, anxiety and depression was 61%, 31% and 18%, respectively. There was a statistically significant association in the CMD correlations between those who reported having workrelated health problems (p-value 0.01) and sleep satisfaction (p-value 0.01). For anxiety, the correlation between age 31-40 (p-value 0.02), work-related employment (p-value 0.05) and depression (p-value 0001) were significant. For depression, the weekly workload of up to 30 hours a week (p-value 0.001). Conclusion: Health professionals had substantial levels of common mental disorders (CMD), anxiety and depression, with a prevalence of CMD identified in 61% of participants. This reinforces the need for measures to protect the mental health of these professionals in order to improve their quality of life disorders (CMD), xix anxiety and depression, with a prevalence of CMD identified in 61% of participants. This reinforces the need for measures to protect the mental health of these professionals when dealing with and combating Covid-19 in the hospital under study.